Comparison of Fracture Strength of Modified PEEK, Nanohybrid Ceramic, Monolithic Zirconium Endocrowns Produced with CAD/CAM System - Ciris, Gulsum Sena; Altintas, Eyyup (Galenos Publ House, 2022)
Objective: The aim of this study; comparison of fracture strength of monolithic zirconium, nanohybrid ceramic and modified polyetheretherketone (PEEK) endocrowns produced with computer-aided design/computer-aided manufacturing (CAD/CAM) system. Materials and Methods: Thirty permanent human first molar teeth of identical anatomical size were collected. After root canal treatment and endocrown preparation were applied to the teeth, they were divided into three groups (n=10). PEEK coping, nanohybrid ceramic and monolithic zirconium, endocrowns were produced by digital methods for each group. The infrastructure of the PEEK group was completed with 1 mm composite to be the same size as the other groups. Cement gap was determined as 100 mu m. After cementation of the endocrowns, the specimens were placed in a chewing simulator, equivalent to 6 months of clinical use. For the fracture strength test, the specimens placed on the universal test device were loaded with a head speed of 1 mm/minute until they broke and the specimens were examined under a stereomicroscope to determine the failure type. Statistical analysis of test data was performed.Results: The highest mean fracture strength of the monolithic zirconium endocrown group (2496.5 +/- 189.12 N), secondly, modified peek endocrown group (1728.2 +/- 139.26 N) and nanohybrid ceramic endocrown group (1248.8 +/- 107.6 N) were determined as the lowest. A statistically significant difference was found between the groups in terms of fracture strength (p<0.05).Conclusion: Modified peek, nanohybrid ceramic, monolithic zirconium endocrowns can be an effective option for the restoration of root canal treated molar teeth with excessive material loss.
Keywords: CAD; CAM; endocrown; fracture strength